Physiological characteristics of cadet girls while studying at the military academy - SLIUSARCHUK, VIKTOR; IEDYNAK, GENNADII; GALAMANZHUK, LESIA; BLAVT, OKSANA; BALATSKA, LARISA; ZORIY, YAROSLAV; NAKONECHNYI, IHOR; MARCHUK, DANIIL; DOTSYUK, LIDIIA; MOLDOVAN, ANDRIY (Journal of Physical Education and Sport, 2021)
The aim of the study was to establish features in the physiological characteristics of cadet girls during each year of study at the military academy. Material and Methods. The study involved 108 girls who were 17-18 years old at the beginning of the study. Physiological characteristics were studied annually throughout the four-year period of study of the same girls in the military academy. Characteristics were recorded at the beginning and end of the first, as well as at the end of each subsequent year during routine medical examinations. The following functional characteristics were studied: blood pressure (systolic and diastolic); heart rate; vital capacity; Ruffier index; Robinson index; vital capacity index; index maximum isometric strength. Empirical data obtained during the surveys of girls were processed by adequate methods of mathematical statistics; used the software package SPSS 20. Results. The analysis of changes in the state of the studied functional characteristics of cadet girls shows their dependence on the period of study and factors related to motivation and parameters of physical activity used in physical education classes at the military academy. At the present stage, the first and last years of study of cadet girls are marked by a positive result in the development of the studied functional characteristics. Some of the leading reasons for this result in the first case is the presence of a generalized stage of adaptation syndrome, in the second case - the motivation of girls to improve their functional characteristics to achieve the highest possible level of their development before starting a career. Conclusions: The results indicate areas for improving the organization, content of physical education of girls - cadets to improve their functional characteristics to the highest possible level, but above all efficiency in the cardiovascular system at rest, respiratory in full oxygen supply, skeletal muscle in excess accumulation in the muscles of structural and energy potentials that increase their working capacity and physical performance
Keywords: girls - cadets, physical education, state of development, body systems, physical performance